PERLINDUNGAN HUKUM HaKI DALAM PERJANJIAN WARALABA DI INDONESIA - Lathifah Hanim (Jurnal Hukum, 2011)
Always related to the provision granting franchise rights to use and or use of certain intellectual property rights, which in this case embodied in the brand, which covers both trademarks and service marks, or indications of origin (indication of origin) and a specific format, formula, characteristics, methods, procedures, procedures, systems etc. that are typically associated with, and which can not be separated from each output or product that is produced and then sold, delivered or traded by using the trademarks, service marks or indications of origin mentioned above, called a trade secret.The problem is how the legal protection of intellectual property rights for the franchisor (the Franchisor) and Franchisee (the Franchisee) in franchise agreements in Indonesia.Franchise agreements is one aspect of legal protection to the parties of the actions harm others, including in providing legal protection for intellectual property rights. This is because the agreement can be a strong legal basis to enforce legal protections for the parties involved in the franchise system. If either party violates the agreement, then the other party can sue the infringing party in accordance with applicable law. Legal protection of intellectual property rights owned by the Parties to the Franchisor (the franchisor) will be better protected if the Franchise Agreement has been set up specifically on IPR protection, which is a pledge of certain restrictions that must be adhered to by the Franchisee (the franchisee), which directly or not directly intended to protect intellectual property rights of the Parties to the Franchisor (the franchisor). The Franchise Agreement which provides IP protection provisions also set Franchisee shall protect trade secrets provided by the franchisor during the term at least 2 (two) years after the franchise period expires. Franchisee shall maintain the rights and interests as holders of rights to the franchisor's brand. Franchisee is prohibited to run any other business which directly competes with the franchisor during the term of business and franchise and for a period of at least 2 (two) years after the franchise period expires. Intellectual Property Rights in the franchise business is also highly protected by the laws relating to intellectual property rights, namely: Copyright Law, Trademark Law, and the Trade Secrets Act.Key words: Franchise Agreement, Legal Protection.